Effect of Tai Chi on Cognitive Performance in Older Adults: Systematic Review and Meta‐Analysis. Issue 1 (2nd January 2014) - Wayne, Peter M.; Walsh, Jacquelyn N.; Taylor‐Piliae, Ruth E.; Wells, Rebecca E.; Papp, Kathryn V.; Donovan, Nancy J.; Yeh, Gloria Y.
<x xml:space="preserve">Abstract</x> Objectives To summarize and critically evaluate research on the effects of Tai Chi on cognitive function in older adults. Design Systematic review with meta‐analysis. Setting Community and residential care. Participants Individuals aged 60 and older (with the exception of one study) with and without cognitive impairment. Measurements Cognitive ability using a variety of neuropsychological testing. Results Twenty eligible studies with a total of 2, 553 participants were identified that met inclusion criteria for the systematic review; 11 of the 20 eligible studies were randomized controlled trials (RCTs), one was a prospective nonrandomized controlled study, four were prospective noncontrolled observational studies, and four were cross‐sectional studies. Overall quality of RCTs was modest, with three of 11 trials categorized as high risk of bias. Meta‐analyses of outcomes related to executive function in RCTs of cognitively healthy adults indicated a large effect size when Tai Chi participants were compared with nonintervention controls (Hedges' g = 0.90; P = .04) and a moderate effect size when compared with exercise controls (Hedges' g = 0.51; P = .003). Meta‐analyses of outcomes related to global cognitive function in RCTs of cognitively impaired adults, ranging from mild cognitive impairment to dementia, showed smaller but statistically significant effects when Tai Chi was compared with nonintervention controls (Hedges' g = 0.35; P = .004) and other active interventions (Hedges' g = 0.30; P = .002). Findings from nonrandomized studies add further evidence that Tai Chi may positively affect these and other domains of cognitive function. Conclusion Tai Chi shows potential to enhance cognitive function in older adults, particularly in the realm of executive functioning and in individuals without significant impairment. Larger and methodologically sound trials with longer follow‐up periods are needed before more‐definitive conclusions can be drawn.